Complex management of multiple facial traumas using a bottom-up approach - Wijaya, Wilson; Sjamsudin, Endang; Sylvyana, Melita (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Blunt trauma, particularly from traffic accidents, is a leading cause of multiple facial fractures. Managing such injuries can be extremely challenging for surgeons, especially when multiple facial regions are involved. Inadequate stabilization of fractured bones may result in permanent deformities. This case report outlines the principles and techniques of managing complex facial trauma, focusing on achieving harmonious bone alignment and balanced occlusion through proper segmental reduction. We present the case of a 28-year-old male with multiple facial fractures sustained in a traffic accident. Clinical and radiological examinations revealed fractures of the left orbital rim, Le Fort I level, left zygomaticomaxillary complex, mandibular symphysis, and right parasymphysis, accompanied by tooth avulsion. The patient underwent open reduction and internal fixation (ORIF) under general anesthesia using a bottom-up approach, followed by four weeks of intermaxillary fixation. This resulted in improved facial contour and satisfactory intermaxillary relationship. Effective management of multiple facial fractures requires comprehensive planning and meticulous technique to restore facial aesthetics, mastication, and anatomical landmarks. This can be achieved through either a top-down or bottom-up approach, depending on the stability of the fractured segments. In this case, ORIF was initiated with mandibular fixation due to the relative stability of the mandibular fragments, supporting the use of a bottom-up strategy. Thorough planning and precise execution are crucial to achieving optimal anatomical and functional outcomes and preserving the patient’s quality of life.